Treatment of distillery wastewater using advanced oxidation processes UX/O3, UV/H2O2 and H2O2/O3 - Dionisio, Mercy Grace A. (2013.)
Distillery industry generates large volume of wastewater that is high in organic strength and has coloured refractory organics. In view of this problem, the feasibility of using advanced oxidation process (AOPs), namely UV/O3, UV/H2O2 and H2O2/O3, to treat distillery wastewater from molasses-based alcohol industrial plant was explored in this study. The efficiency of the AOPs in the degradation of COD and the color at varying pH, H2O2 dosage and initial wastewater concentration was investigated at constant ozone supply of 606 mg for two hours of experimental batch run. In all runs, the COD and color removal were highest at the maximum applied dose of hydrogen peroxide in the system (1,000 mg/L). At the natural pH of the wastewater (pH 4.6~4.9) the effectiveness of each AOP followed the sequence: H2O2/O3 > UV/H2O2 > UV/O3 > O3 > UV-C. Color removal is best at the natural pH (4.6~4.9) for all AOP experimental runs. In H2O2-based process (H2O2/O3 and UV/H2O2) COD removal rate is best at acidic pH (4.6). UV/O3 process is enhanced by operation at alkaline pH (10). H2O2/O3 process is the most effective AOP. It removed 91% color and 60% COD (initial VOD level of 1,000 mg/L).It also removed 32%, 27% and 35% TKN, NH4-N and DON, respectively. The COD removal in all AOPs tested follow second-order reaction rate equation while the color removal rate is first-order. The fastest COD removal rate constant (1x10-5 ppm-1 min-1) and color removal rate constant (2x10-2 min-1) were in the H2O2/O3 process at the highest oxidant concentration used (COD/H2O2 ratio of 1 H2O2/O3 ratio is 1.7).
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman
Keywords: Sewage -- Purification